ORGANIZATIONAL CULTURE, COMPETENCE, AND SUPPORT INFLUENCES ON COMMITMENT AND PERFORMANCE: AN EMPIRICAL STUDY AT PTPN III - Amran Hidayat; Agung Budi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze the influence of organizational culture, competence, and perceived organizational support on organizational commitment and its implications for employee performance at PT Perkebunan Nusantara III. The population of this study consisted of 1,245 employees of PT Perkebunan Nusantara III. Using the Slovin formula with a 5 percent error level, 303 respondents were selected as research samples through proportionate random sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that organizational culture, competence, and perceived organizational support have a positive and significant effect on organizational commitment. Furthermore, organizational commitment has a significant positive effect on employee performance. Organizational commitment also acts as a mediating variable in the relationship between organizational culture, competence, perceived organizational support, and employee performance. The limitation of this study lies in the use of cross–sectional data and the focus on a single company. Future research is recommended to involve multiple organizations and add other variables such as leadership style and job satisfaction.